2003
DOI: 10.1038/sj.mp.4001212
|View full text |Cite
|
Sign up to set email alerts
|

Association of D4 dopamine receptor gene and serotonin transporter promoter polymorphisms with infants' response to novelty

Abstract: Effects of DRD4 and 5-HTTLPR length polymorphisms have been reported on neonatal and infant temperament as well as adult personality traits. The 7-repeat form of the DRD4 III exon VNTR polymorphism has been associated with childhood ADHD, and recently we have reported its link with attachment disorganization in a nonclinical population of infants. Here, we report associations of these polymorphisms with infant temperament at 12 months of age. Maternal accounts of temperament and observed response to novelty we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
85
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 42 publications
8
85
0
3
Order By: Relevance
“…15 Evidence linking the 7-repeat allele of the DRD4 gene with infant temperament traits of negative emotionality [16][17][18] and maladaptive behavioral problems, especially attention deficit hyperactivity disorder (ADHD) in children, is being accumulated.…”
Section: 13mentioning
confidence: 99%
See 2 more Smart Citations
“…15 Evidence linking the 7-repeat allele of the DRD4 gene with infant temperament traits of negative emotionality [16][17][18] and maladaptive behavioral problems, especially attention deficit hyperactivity disorder (ADHD) in children, is being accumulated.…”
Section: 13mentioning
confidence: 99%
“…26,27 We have previously speculated about the role of potential genetic interaction between the structural and regulatory polymor- phisms in the mixed results of replication studies of effects of the DRD4 exon III VNTR polymorphism. 28 To investigate the possible effects of such an interaction on attachment behavior, 95 children (41 girls and 54 boys) participating in the longitudinal Budapest Infant Parent Study (BIPS), already genotyped for the 48-basepair repeat polymorphism in the third exon of the DRD4 gene, 8,17 were also genotyped for the −521 C/T SNP. Frequencies of the C and T alleles in the BIPS sample were 0.489 and 0.511, respectively (Table 1).…”
Section: -21mentioning
confidence: 99%
See 1 more Smart Citation
“…117,[160][161][162][163][164][165] As we first noted, 164,165 the study of temperament traits in children offers the opportunity to study gene effects at a time in development when environmental effects are conjectured to be minimal and genetic associations might be more robustly demonstrated.…”
mentioning
confidence: 99%
“…who examined a two-locus haplotype consisting of the exon III repeat and the C-521T promoter polymorphism in family trios studied for disorganized attachment (see Lakatos et al [115][116][117] for their earlier work and a Dutch study 118 that reported a failure to replicate the association between attachment and DRD4), an early behavioral measure related to temperament. These authors showed that the transmission bias in the larger secure attachment group of infants was because of the low-rate transmission of the C-521T 'T':exon 3 seven repeat haplotype, suggesting that not carrying this haplotype may act as a resilience factor in the optimal development of early attachment.…”
mentioning
confidence: 99%